Eric Touya De Marenne. Francophone Women Writers: Feminisms, Postcolonialisms, Cross-Cultures. Lanham, MD: Lexington, 2013. 195 pp. - Nancy E. Wardle (Studies in 20th & 21st Century Literature, 2015)
Review of Eric Touya De Marenne. Francophone Women Writers: Feminisms, Postcolonialisms, Cross-Cultures. Lanham, MD: Lexington, 2013. 195 pp.
Keywords: book review; Eric Touya De Marenne; Francophone; women writers; feminism; postcolonial